An overview of crisis management, decision-making, and sports media concept / Fakrulnizam Jafri and Azizul Halim Yahya - Jafri, Fakrulnizam; Yahya, Azizul Halim (Faculty of Communication & Media Studies, 2021)
conceptual article discusses the relationship between crisis communication management, decision-making, and sports media. The lack of academic research related to crisis communication management and sports media attracted the author's attention in the writing of this article. There is a growing communication management crisis emerging in the sports industry in general and in the football industry, especially where the crisis communications area has become increasingly valuable in academic research in sports and media. This article highlighted some of the backgrounds, concepts, and issues of crisis management in institutions and sports organizations which divided into three phases, namely (i) pre-crisis, (ii) crisis response, and (iii) post-crises. In addition, this article also provides a brief statement of the decision-making process as described by Fotr & Svecova. The concept of relationships between sports and media highlights media competition knowledge and decision-makers in gaining broadcast media rights to billions of viewers for major sporting events around the world. Finally, this article also describes the Situation Crisis Communication Theory (SCCT) introduced by Professor Coombs in the management of the communications crisis and sports media.